Effects of helical structures formed by the binding arms of DNAzymes and their substrates on catalytic activity. - Ota, N (1998)
As a part of our efforts to clarify structure-function relationships in reactions catalyzed by deoxyribozymes (DNAzymes), which were recently selected in vitro , we synthesized various chimeras and analyzed the kinetics of the corresponding cleavage reactions. We focused on the binding arms and generated helices composed of binding arms and substrates that consisted of RNA and RNA, of RNA and DNA or of DNA and DNA. As expected for the rate limiting chemical cleavage step in reactions catalyzed by DNAzymes, a linear relationship between log( k cat) and pH was observed. In all cases examined, introduction of DNA into the binding helix enhanced the rate of chemical cleavage. Comparison of CD spectra of DNAzyme. substrate complexes suggested that higher levels of B-form-like helix were associated with higher rates of cleavage of the substrate within the complex. To our surprise, the enhancement of catalytic activity that followed introduction of DNA into the binding helix (enhancement by the presence of more B-form-like helix) was very similar to that observed in the case of the hammerhead ribozymes that we had investigated previously. These data, together with other observations, strongly suggest that the reaction mechanism of metal-ion-dependent DNAzymes is almost identical to that of hammerhead ribozymes.